On the Betti number of the union of two generic map images - Biasi, Carlos; Libardi, Alice K. M. [UNESP]; Saeki, Osamu (Elsevier B.V., 1999)
Let f: M --> N and g: K --> N be generic differentiable maps of compact manifolds without boundary into a manifold such that their intersection satisfies a certain transversality condition. We show, under a certain cohomological condition, that if the images f(M) and g(K) intersect, then the (upsilon + 1)th Betti number of their union is strictly greater than the sum of their (upsilon + 1)th Betti numbers, where upsilon = dim M + dim K - dim N. This result is applied to the study of coincidence sets and fixed point sets. (C) 1999 Elsevier B.V. B.V. All rights reserved.
Keywords: generic map; Betti number; intersection map; coincidence set; fixed point set